The p22phox Polymorphism C242T Is Not Associated with Peripheral Malondialdehyde and Superoxide Dismutase Levels in Healthy Korean Adults - Su-Youn CHO; Wi-Young SO; Hee-Tae ROH (Iranian Journal of Public Health, 2019)
No Abstract###